BIOECOLOGY STUDY OF THE SPECIES PARATETTIX MERIDIONALIS (TETRIGIDAE, ORTHOPTERA) IN CONSTANTINE REGION, EASTERN ALGERIA - C, Derrouiche*,; N., Benkenana,; , Guerfi I. (university of eloued جامعة الوادي, 2020)
The Constantine region is located in the semi-arid bioclimatic stage. The locust and grasshoppers fauna in this region totals the presence of five families and twelve sub-families. The family Tetrigidae is represented by only one species; Paratettix meridionalis (Rambur, 1838). It is a small species, black with white spots. The pronotum is elongated and often covers the abdomen to the apex. A large number of P.meridionalis was collected near to water source. We performed morphometric analyzes. Surveys and monitoring of this grasshopper during the study period indicate that it has two generations. As part of the diet study of this species, we identified 14 plants in our study station. Results of the analysis of faeces of males and females show that it consumes plants that belong to two essential families: Asteraceae and Poaceae. The Tetrigidae family still not well-known in Algeria.
artical
Keywords: Asteraceae, Chaab Erssas station, Diet, Grasshoppers, Morphometric analyses.